Severity and Determinants of Anemia in TB/HIV Coinfected Adults at Mekelle, Ethiopia: Hospital Based Retrospective Study - Kebede Embaye Gezae; Kiflom Hagos; Assefa Ayalew Gebreslassie (Journal of Tropical Medicine)
Background. Anemia has up to 87% prevalence in high tuberculosis (TB) and human immunodeficiency virus (HIV) burden settings of the sub-Saharan Africa (SSA) including Ethiopia. It increases lost to follow-up (LTFU) rate, reduces quality of life, and shortens the survival of TB/HIV coinfected patients. However, there is limited information on severity level and determinants of anemia in TB/HIV coinfected adults in the study setting in particular. Therefore, this study is aimed to assess severity level and determinants of TB/HIV-associated anemia. Methods. A hospital based retrospective study was conducted among 305 TB/HIV coinfected adults who enrolled for antiretroviral therapy (ART) from January, 2009 to December, 2016 in two public hospital of Mekelle, Ethiopia, by reviewing ART register. A multiple logit model was fitted to identify the baseline determinants of anemia using 95% confidence level or 5% level of significance for adjusted odds ratio (AOR). Results. In the current study, the cumulative baseline prevalence of anemia was 59.0% (95% CI: 53.3%–64.6%). Considering severity level, the prevalence was 6.2%, 28.2%, and 24.6% for severe, moderate, and mild anemia, respectively. Being female (AOR = 0.380; 95% CI: 0.226–0.640), body mass index (AOR = 0.913; 95% CI: 0.836–0.998) reduces the odds of developing anemia whereas baseline ambulatory functional status (AOR = 2.139; 95% CI: 1.189–3.846), bedridden functional status (AOR = 2.208; 95% CI: 1.002–4.863), HIV clinical stage III (AOR = 2.565; 95% CI: 1.030–6.384), and HIV clinical stage IV (AOR = 2.590; 95% CI: 1.006–6.669) increased the odds of developing anemia for TB/HIV coinfected adults. Conclusions. In the current study, significant TB/HIV-associated severe anemia was assessed which accounted for nearly one-ninth of all anemia cases while nearly half were moderate anemia. Therefore, curious attention has to be given for the management of TB/HIV-associated severe anemia in particular and anemia in general to reducing anemia associated bad outcomes most importantly death.